The global epidemiology of gastrointestinal cancer burden attributable to dietary risks: a systematic analysis of the Global Burden of Disease Study 2021 - Yao, Laiang; Nie, Jiao; Kong, Lingjian; Shao, Shuai; Xu, Xiangming (Frontiers in Nutrition, 2025)
BackgroundGastrointestinal (GI) cancers collectively account for over 30% of global cancer-related mortality, with diet and nutrition playing crucial roles in their development. We investigated the burden, trends and disparities of GI cancers attributable to dietary risks.MethodsData was collected from the Global Burden of Disease Study 2021. Disease burden was measured by deaths and disability-adjusted life years (DALYs), along with age-standardized rates (ASRs). Joinpoint regression, with average annual percent changes (AAPCs) were used to assess temporal trends. ARIMA models were employed to project the ASRs till 2040.ResultsBetween 1990 and 2021, the AAPC of the age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) of colorectal cancer (CRC) attributable to dietary risks were −0.87 (95% CI: −0.89, −0.84) and −0.88 (95% CI: −0.90, −0.86). Esophageal cancer showed the greatest declining rate, with ASRs declining more than 3% annually. The ASRs of stomach cancer decreased by more than 2% per year. The burden of stomach cancer and esophageal cancer were highest among low and low-middle SDI countries and regions, particularly East Asia and Sub-Saharan Africa, respectively. High-SDI countries and regions showed the highest burden of CRC but the greatest declining rates. Future projections suggest constant decreasing burden for stomach cancer and CRC, but stable trends for esophageal cancer.ConclusionDiet-attributed GI cancer remains a significant public health challenge globally, especially among low SDI and lower-middle SDI countries. Given the disparity of risk exposures and disease burden, we recommend promoting screening practices and improving healthcare accessibility in low SDI countries, while emphasizing lifestyle modifications in higher SDI countries to combat this pressing issue.